A prospective study of pre-trauma risk factors for posttraumatic stress disorder and depression - Wild, J; Smith, K; Thompson, E; Bear, F; Lommen, M; Ehlers, A (Cambridge University Press, 2016)
Background: It is unclear which potentially modifiable risk factors best predict posttrauma psychiatric disorders. We aimed to identify pre-trauma risk factors for posttraumatic stress disorder (PTSD) or major depression (MD) that could be targeted with resilience interventions. Methods: Newly recruited paramedics (N=453) were assessed for history of mental disorders with structured clinical interviews within the first week of their paramedic training and completed self-report measures to assess hypothesized predictors. Participants were assessed every four months for two years to identify any episodes of PTSD and MD; 386 paramedics (85.2%) participated in the follow-up interviews. Results: Thirty-two participants (8.3%) developed an episode of PTSD and 41 (10.6%) an episode of MD during follow-up. In all but 9 cases (2.3%), episodes had remitted by the next assessment four months later. At two years, those with episodes of PTSD or MD during follow-up reported more days off work, poorer sleep, poorer quality of life, greater burn-out; and greater weight-gain for those with PTSD. In line with theories of PTSD and depression, analyses controlling for psychiatric and trauma history identified several pretrauma predictors (cognitive styles, coping styles and psychological traits). Logistic regressions showed that rumination about memories of stressful events at the start of training uniquely predicted an episode of PTSD. Perceived resilience uniquely predicted an episode of MD. Conclusions: Participants at risk of developing episodes of PTSD or depression could be identified within the first week of paramedic training. Cognitive predictors of episodes of PTSD and MD are promising targets for resilience interventions.